Moldova Poverty and Shared Prosperity Update 2018 - Cojocaru, Alexandru (World Bank, Washington, DC, 2018)
This note provides an update of recent poverty and shared prosperity dynamics, and some of the underlying drivers, as well as introducing the new international poverty thresholds that are currently in use. The purpose of the update is to take advantage of the release of Household Budget Survey (HBS) data for the 2016 survey round. The previous poverty and shared prosperity update, release in 2017, updated poverty and shared prosperity trends up to 2015. The first section discusses the overall progress poverty reduction and shared prosperity up to 2016 – the latest available household budget survey data. Notably, the poverty dynamics are presented, for the first time, using PPP values based on the 2011 ICP exercise, and using the newly adopted Income Class poverty thresholds of $3.3/day and $5.5/day. For the purposes of this note, we focus on the $5.5/day threshold, but the section also presents a comparative analysis of poverty dynamics based on old and new thresholds. Because this is the first time when internationally-comparable poverty and shared prosperity statistics for Moldova are presented based on the ICP 2011 PPP conversion factors, and relying on newly defined income-group based thresholds, the introduction has a brief discussion of the reasons behind the change in the World Bank’s poverty methodology used for global poverty monitoring, and the implications of this change for poverty trends over time and for the absolute levels of poverty reported in Moldova. Section 2 discussed the major drivers of shared prosperity during the 2011-2016 period. Section 3 examines the profile of poor and vulnerable populations, their asset endowments, and changes in this profile in recent years.